Did we find alternate to GDP to measure national progress? Analysis of Harvard University’s social progress index - SIDDIQUI, Ahmad F.; WASEEM, Ansar; MAMOON, Dawood (Turkish Economic Review, 2017)
Abstract. For major part of the preceding century, Economic Measures such as GDP, GNI etc were considered to measure economic as well as social and human progress of a country. However, scholars have raised concerns over the sufficiency of these economic measures. This propelled scholars to develop alternate measures for social improvement and human capability development. Consequently, indices such as Social Progress Imperative (SPI) and Human Development Index (HDI) were developed by renowned authors. However, little work is done to check effect of social progress on susceptibility against human trafficking and modern slavery, and business opportunities in the nation. Further, there is almost no empirical evidence which suggest that SPI is better scale than GDP or HDI in predicating different social measure. Therefore, data of 124 countries regarding SPI, HDI, GDP, Vulnerability to Enslavement, and Distance to Frontier score was collected for Year 2014. Secondary data analysis was performed and Simple Regression analysis was carried out on data for hypothesis testing. As proposed, a positive relationship of SPI and Ease of Doing Business was observed whereas negative relation was found between SPI and Vulnerability of Enslavement. In addition, SPI explain variation in both Vulnerability of Enslavement and Ease of Doing Business better than GDP and HDI, thereby providing evidence of its superior representation of social measures. Keywords. Social progress, Human development, Ease of doing business, Vulnerability to slavery, SPI, HDI. JEL. O15.